If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(3) + 9 = 27 Reorder the terms for easier multiplication: 3x + 9 = 27 Reorder the terms: 9 + 3x = 27 Solving 9 + 3x = 27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 3x = 27 + -9 Combine like terms: 9 + -9 = 0 0 + 3x = 27 + -9 3x = 27 + -9 Combine like terms: 27 + -9 = 18 3x = 18 Divide each side by '3'. x = 6 Simplifying x = 6
| X^2+3=5x(x+6) | | 4(3+m)=8(6m+7) | | (x+9i)(x-9i)=0 | | 4x+7=22-x | | 7z-1=z+22 | | 3v+2y=100 | | 6cosx=4sinx | | (-x-9i)(x+9i)=0 | | -5x-1=29+5x | | -4y+7x=-24 | | 7x-(3+4x)= | | 3a-15=-14 | | 3c+18=14 | | 3r^2+25r+8=0 | | 14x-29=6x+29 | | C=.15M+15 | | 57+66+x=180 | | 1/8logx=-5/3 | | 13-2x=93 | | -5(3x-9)=150 | | 66+x+x=180 | | 1/2X-10=6 | | y^2-8y=20 | | 9x-2=98 | | (-4i)(2i)(-3i)= | | 6/5÷5/8 | | 7(d+2)=2(d-7)+5d | | 2X+Y=356 | | 7xy*9=0 | | -6x+4=-41+3x | | -3p+8=14 | | 3-1/8=9/2 |